2021
DOI: 10.3389/fphys.2021.596060
|View full text |Cite
|
Sign up to set email alerts
|

Is Ultra-Short-Term Heart Rate Variability Valid in Non-static Conditions?

Abstract: In mobile healthcare, heart rate variability (HRV) is increasingly being used in dynamic patient states. In this situation, shortening of the measurement time is required. This study aimed to validate ultra-short-term HRV in non-static conditions. We conducted electrocardiogram (ECG) measurements at rest, during exercise, and in the post-exercise recovery period in 30 subjects and analyzed ultra-short-term HRV in time and frequency domains by ECG in 10, 30, 60, 120, 180, and 240-s intervals, and compared the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 61 publications
3
18
0
Order By: Relevance
“…The power spectrum of HRV was not investigated due to inconsistencies in high frequency power (HF) compared to RMSSD, notably in the early phase of post-exercise recovery (Baek et al 2015 ; Hung et al 2020 ). Furthermore, Kim et al ( 2021 ) have recently shown that segments of at least 120 s were required to correctly quantify HF immediately after exercise completion, hence ruling out the possibility of obtaining segments of sufficient duration during the 5 min post-exercise recording in the present study. The relevance of analyzing RMSSD rather than HF immediately after exercise completion is also related to excellent agreement and accuracy of HRV in time domain analyses (Baek et al 2015 ; Hung et al 2020 ).…”
Section: Methodsmentioning
confidence: 84%
See 1 more Smart Citation
“…The power spectrum of HRV was not investigated due to inconsistencies in high frequency power (HF) compared to RMSSD, notably in the early phase of post-exercise recovery (Baek et al 2015 ; Hung et al 2020 ). Furthermore, Kim et al ( 2021 ) have recently shown that segments of at least 120 s were required to correctly quantify HF immediately after exercise completion, hence ruling out the possibility of obtaining segments of sufficient duration during the 5 min post-exercise recording in the present study. The relevance of analyzing RMSSD rather than HF immediately after exercise completion is also related to excellent agreement and accuracy of HRV in time domain analyses (Baek et al 2015 ; Hung et al 2020 ).…”
Section: Methodsmentioning
confidence: 84%
“…Ln RMSSD were calculated for each 30 s segment in recovery, i.e. Ln RMSSD 30 , as done previously (Goldberger et al 2006 ) and recently recommended by Kim et al ( 2021 ). The power spectrum of HRV was not investigated due to inconsistencies in high frequency power (HF) compared to RMSSD, notably in the early phase of post-exercise recovery (Baek et al 2015 ; Hung et al 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…These results were consistent with Castald's (Castaldo et al, 2019) investigation that NNmean and HF displayed consistency across all of the excerpt lengths (30 s, 1 min, 2 min, 3 min, and 5 min) for mental stress assessment. However, Jin Woong et al (Kim et al, 2021) studied UST HRV in non-static conditions by comparing UST HRV features (10, 30, 60, 120, 180, and 240-s) with those from 5-min HRV, the results showed that UST HRV variables derived from the static condition could not applied to the non-static conditions of daily life. Similarly, the CC, Trans, Dia and GE of VG features remained stable in both activated and inactivated segments across all data lengths, implying that these VG features could reveal the dynamical changes caused by the adjustment of autonomous neural system from UST segments.…”
Section: Figurementioning
confidence: 99%
“…HRV is a sensitive tool that assesses the time difference between consecutive heart beats to evaluate autonomic nervous system modulation [40,41]. Accumulating data suggest that ultra-short-range HRV can be successfully derived from as low as 30 s of human ECG [42,43] and pulse rate variability (estimation of variation in heart rate (HR) from photo plethysmography) has recently been successfully measured from the rat tail [44]. Potentially, measurement of HRV from tail-cuffs would be a useful reduction, refinement or replacement (3Rs) laboratory animal welfare advancement, since surgery is not required.…”
Section: Introductionmentioning
confidence: 99%